AJARAN SUSILA PADA TOKOH BIMA LAKON DEWA RUCI DALAM PERTUNJUKAN WAYANG KULIT UNTUK MENINGKATKAN MUTU PENDIDIKAN DI ABAD 21 - Diwan, Diwan; Kiriana, I Nyoman; Sujanayasa, I Made (Institut Hindu Dharma Negeri Denpasar, 2019)
Wayang Kulit is one of the world's masterpieces because it contains a variety of values, ranging from life philosophy, ethics (moral), spirituality, music (gamelan, gending), to the aesthetics of very complex art forms. This has led to the staging of Balinese shadow puppets not only as a spectacle but also as a guide for the community. Wayang offers a very interesting educational method, because it teaches the values of religious and ethical teachings, as well as the values of life that should be captured by the audience through the play as well as the characters as role models. Like the play Dewa Ruci in the shadow puppet show. This play illustrates the spiritual journey of the Bima character who attains the level of inner and outer chastity. Bima's figure gives anualization of moral teachings between others: Guru Susrusa, Satya, Tri Kaya Parisudha, Wiweka and Tapa, this moral teaching is the provision to improve the quality of education in the 21st century.